2002
DOI: 10.1155/np.2002.27
|View full text |Cite
|
Sign up to set email alerts
|

Vision After Early-Onset Lesions of the Occipital Cortex:II. Physiological Studies

Abstract: SUMMARYIn one of two patients (MS and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…transcallosal, major forceps, or commissural tracts) [47,52]. Such interhemispheric connections may play major roles during visual recovery, particularly after early-onset unilateral lesions, as documented previously in animal studies [53].…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…transcallosal, major forceps, or commissural tracts) [47,52]. Such interhemispheric connections may play major roles during visual recovery, particularly after early-onset unilateral lesions, as documented previously in animal studies [53].…”
Section: Resultsmentioning
confidence: 76%
“…These more laterally located activation could be part of extrastriate cortex, mainly in V2 area, as defined retinotopically in the adult visual cortex [43,44] and recently shown in children [45]. Although some studies have suggested that activation of the striate cortex was a major sign of visual recovery [46,47], activations limited to extrastriate areas have been reported in patients with brain lesions. Thus, in patients with occipital lobe epilepsy, extrastriate visual responses to full-field visual stimulation were observed with fMRI [48].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The differences, on the other hand, might be useful for understanding the pathogenesis of the deficit and the possible mechanisms of functional recovery (Knyazeva et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Known as neural plasticity, this process is considered a fundamental feature of all brain tissue. Initially demonstrated in animals (for review see Destexhe & Marder, 2004), in humans it has been documented most clearly within the motor cortices during the acquisition and practice of motor skills (Pascual-Leone et al, 1995;Ungerleider, Doyon, & Karni, 2002) and in the visual system after lesions to the occipital cortex (Kiper, Zesiger, Maeder, Deonna, & Innocenti, 2002;Knyazeva, Maeder, Kiper, Deonna, & Innocenti, 2002;Rahi et al, 2002). Human neural plasticity research began with the assumption that the phenomenon is most common in young children (Chugani, Muller, & Chugani, 1996), but even the adult cortex is now thought to undergo continual plastic remodeling (Paulsen & Sejnowski, 2000).…”
Section: Neural System Change and Reorganization In Humansmentioning
confidence: 99%